ANALISIS SISTEM TATA UDARA DI DALAM KABIN KENDARAAN MINIBUS DENGAN MENGGUNAKAN PERANGKAT LUNAK COMPUTATIONAL FLUID DYNAMICS - Soelaiman, T. A Fauzi; Aritonang, Andini (Mesin, 2005)
The aim of this research is to establish an analysis of an air conditioning system in a minibus vehicle cabin through some series of numerical simulations using a Computational Fluid Dynamics software. Two three-dimensional models of the vehicle were used in the simulations. The first model is a minibus without any passenger, and the second model is a minibus with seven passengers. In this research, the passenger model was considered as another cooling load source, therefore an analysis of the cooling effect experienced by passenger was not performed. A calculation of cooling load was also done to determine the maximum cooling load, using the weather data of Jakarta city throughout the year 2002. An experiment was done using an actual vehicle to validate the model. The maximum error of temperature reading between experiment and simulation was calculated and gave an acceptable maximum error of 10%. The simulation in this step was performed using the first model and steady calculation. A series of simulations were also done to analyze the air conditioning system performance under maximum cooling load. These simulations were done by varying the mass flow rates of the air entering the cabin, using the second model and transient calculations. The temperature and velocity contours acquired from these simulations were able to give good understanding of correlations between the factors influencing the air condition in the cabin.